The Factor-Shares Cycle and its Relation to the Business Cycle - William A. Jackson (Business Cycles in Economics: Types, Challenges and Impacts on Monetary Policies, 2014)
The traditional assumption of constant factor shares (Bowley's Law) may be misleading, for factor shares do vary in both the short run and the long run. The present chapter looks at short-run factor share movements, asking how they relate to the business cycle. Theoretical arguments differ about whether profit and wage shares are procyclical or counter-cyclical, and empirical evidence too yields no neat conclusions. On average, factor share movements roughly offset each other while adhering to a factor-shares cycle, which has similar periodicity to the business cycle but is out of phase with it – the profit share reaches a peak before the top of the cycle and a trough before the bottom of the cycle. Recent experience in developed countries, marked by financialisation, a rising profit share and financially induced recession, has changed the factor-shares cycle. Pressure on the wage share has softened profit squeezes and shifted the cycle towards an underconsumption mode with a procyclical profit share and greater risks of financial instability.
Keywords: E11; E12; E25; E32; 330; factor shares; business cycles; financialisation; underconsumption; financial instability